Study of College of Engineering facilities for microconcrete structural models analysis - Suthdatumprapah, Pinij (1975)
This research is divided into two aspects. The first aspect is to ascertain whether the facilities, of the College of Engineering, University of the Philippines, are adequate for fabrication and testing of structural reinforced microconcrete models. The second aspect consists of making and testing the models.
This thesis discusses the availability of model materials and their properties, the fabrication of the model, and the techniques of model testing used. The results of tests on the model materials and the model tests are reported.
Mimeographed.
Thesis (M.S. Civil Engineering)--University of the Philippines Diliman
Keywords: University of the Philippines (Diliman) -- College of Engineering; Structural frames -- Models; Engineering laboratories -- Evaluation. -- Philippines; Education -- Research -- Laboratories -- Evaluation